Inflationary household uncertainty shocks - Gene Ambrocio (Bank of Finland, 2022)
I construct a novel measure of household uncertainty based on survey data for European countries. I show that household uncertainty shocks do not universally behave like negative demand shocks. Notably, household uncertainty shocks are largely inflationary in Europe. Further analysis, including a comparison of results across countries, suggest that factors related to average markups along with monetary policy play a role in the transmission of household uncertainty to inflation. These results lend support to a pricing bias mechanism as an important transmission channel.
urn:nbn:fi:bof-202202141057
Keywords: D84; E30; E52; E71; 330; uncertainty; inflation; surveys of expectations